Selective apoptosis induction in MCF-7cell line by truncated minimal functional region of Apoptin - Lim, Shen Ni; Allaudin, Zeenathul Nazariah; Mohd Lila, Mohd Azmi; Othman, Abas Mazni; Othman, Fauziah (BioMed Central, 2013)
Background: Chicken Anemia Virus (CAV) VP3 protein (also known as Apoptin), a basic and proline-rich protein has a unique capability in inducing apoptosis in cancer cells but not in normal cells. Five truncated Apoptin proteins were analyzed to determine their selective ability to migrate into the nucleus of human breast adenocarcinoma MCF-7 cells for inducing apoptosis. Methods: For identification of the minimal selective domain for apoptosis, the wild-type Apoptin gene had been reconstructed by PCR to generate segmental deletions at the N’ terminal and linked with nuclear localization sites (NLS1 and NLS2). All the constructs were fused with maltose-binding protein gene and individually expressed by in vitro Rapid Translation System. Standardized dose of proteins were delivered into human breast adenocarcinoma MCF-7 cells and control human liver Chang cells by cytoplasmic microinjection, and subsequently observed for selective apoptosis effect. Results: Three of the truncated Apoptin proteins with N-terminal deletions spanning amino acid 32–83 retained the cancer selective nature of wild-type Apoptin. The proteins were successfully translocated to the nucleus of MCF-7 cells initiating apoptosis, whereas non-toxic cytoplasmic retention was observed in normal Chang cells. Whilst these truncated proteins retained the tumour-specific death effector ability, the specificity for MCF-7 cells was lost in two other truncated proteins that harbor deletions at amino acid 1–31. The detection of apoptosing normal Chang cells and MCF-7 cells upon cytoplasmic microinjection of these proteins implicated a loss in Apoptin’s signature targeting activity. Conclusions: Therefore, the critical stretch spanning amino acid 1–31 at the upstream of a known hydrophobic leucine-rich stretch (LRS) was strongly suggested as one of the prerequisite region in Apoptin for cancer targeting. Identification of this selective domain provides a platform for developing small targets to facilitating carrier-mediated-transport across cellular membrane, simultaneously promoting protein delivery for selective and effective breast cancer therapy.